In vitro functional characterization of missense mutations in the LDLR gene - Silva, S. (2012)
Mutations in the LDL receptor gene are the major cause of familial hypercholesterolaemia (FH) but it has been previously shown that the simple finding of a variation in the coding sequence of the LDLR does not confirm that it is the actual cause of FH. The pathogenicity of five missense alterations in the LDLR gene coding sequence found in a previous epidemiologic study was investigated.